The theory of value and earnings, and an introduction to the Ball‐Brown analysis* - OHLSON, JAMES A. (Contemporary Accounting Research, 1991)
Abstract. The paper develops a simple and parsimonious model that relates earnings and unexpected earnings to market returns. The analysis emphasizes that any model under uncertainty must be consistent with the theory of value, earnings, and dividends under certainty (i.e., Hicksian income theory). An extension of this theory exists such that the model subsumes uncertainty. The Hicksian approach is useful because it embeds key dividend irrelevancy concepts due to Modigliani and Miller (1961), and these can be retained under uncertainty. An interesting empirical proposition can be inferred from the model: earnings, rather than the change in earnings, ought to serve as a premier exploratory variable of returns. This contention is consistent with some recent empirical findings due to Easton and Harris (1991). Résumé. L'auteur élabore un modèle simple et parcimonieux qui relie les bénéfices, et les bénéfices imprévus, aux rendements du marché. L'analyse met en relief le fait que tout modèle en situation d'incertitude doit être conforme á la théorie de la valeur, des bénéfices et des dividendes en situation de certitude (c'est‐á‐dire la théorie hicksienne des bénéfices). Cette théorie peut être élargie de telle sorte que le modèle tienne compte de l'incertitude. L'utilité de l'approche hicksienne tient au fait qu'elle englobe les concepts clés de non‐pertinence relatifs au dividende que l'on attribue á Modigliani et Miller. et que ces concepts peuvent être appliqués en situation d'incertitude. Ce modèle permet de formuler une proposition empirique intéressante: les bénéfices, plutôt que l'évolution des bénéfices, doivent servir de première variable exploratoire des rendements. Cette affirmation est conforme aux résultats empiriques récemment obtenus pas Easton et Harris.